A challenging future for the employment relationship: time for affirmation or alternatives (Geneva, 2016)
"This note discusses the evolution of the employment relationship, the stresses posed by the changing organization of work, the prognosis for fundamental alteration of the relationship, and regulatory challenges in providing adequate protection to workers in evolving employment relationships."